2021
DOI: 10.1177/26323524211051753
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and outcomes of complementary therapies in hospice care: an integrative review

Abstract: Complementary therapies are increasingly integrated into hospice care, emphasizing the need to examine the evidence regarding implementation and effects on end-of-life outcomes. This review synthesizes the evidence regarding the implementation of complementary therapies and effects on end-of-life outcomes in hospice care. Whittemore and Knafl’s five-step integrative review process was applied. Using predefined search terms, research-based articles between 2006 and 2020 were reviewed. Twenty-three quantitative/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…Dingley et al . 18 in their integrative review reported that a number of studies revealed statistically significant improvements in symptoms such as pain and discomfort following patient access to biofield therapies such as massage and acupuncture. Subsequently, it is important that hospice care provision continues to offer access to non-traditional forms of treatments for both patients and family-caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Dingley et al . 18 in their integrative review reported that a number of studies revealed statistically significant improvements in symptoms such as pain and discomfort following patient access to biofield therapies such as massage and acupuncture. Subsequently, it is important that hospice care provision continues to offer access to non-traditional forms of treatments for both patients and family-caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…A range of mind-body and other complementary therapies are also quite often used with people living with advanced cancers. This literature was summarized in a 2021 review, which synthesized the evidence regarding the implementation of complementary therapies on end-of-life outcomes in hospice care (Dingley et al 2021). Twenty-three quantitative or mixed-method studies across eight countries were included.…”
Section: Complementary Therapiesmentioning
confidence: 99%
“…Focusing on caregivers of patients with advanced cancer, it has been previously shown that music has benefits on symptoms of anxiety, fatigue, depression, and blood volume pulse amplitude [28,29]. However, despite the importance of quality of life as a health indicator, to our knowledge, no previous clinical trials have been performed to evaluate the advantages of music for family caregivers of palliative-care patients in the home [30].…”
Section: Introductionmentioning
confidence: 99%